2018
DOI: 10.21614/sgo-23-1-79
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculated Focal Nodular Hyperplasia of the Liver

Abstract: Focal nodular hyperplasia (FNH) is the second most common type of benign liver tumour, and it is more frequently encountered in young women and the right hemi-liver. Most patients are asymptomatic, and there is no malignant potential. Thus, the current guidelines do not recommend any treatment for uncomplicated FNH, and surgery is indicated only for some atypical patients (with complications or uncertain diagnosis). Pedunculated forms are atypical, rare features of FNH and appear to be more frequently associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…(2018) [ 7 ] Female/3 Abdominal distension 5.9 cm Right hepatic lobe Normal US, CT, and MRI Surgery N/A No (history of preterm birth) Martiniuc et al . (2018) [ 13 ] Female/40 Asymptomatic 4.2 cm × 5 cm Seg 3 Normal US and contrast enhanced CT Surgery No complications No Navarini et al . (2020) [ 6 ] Female/26 Acute abdomen and a palpable mass in the epigastrium 13 cm × 7 cm Left hepatic lobe N/A MRI Surgery N/A N/A Alfayez et al .…”
Section: Discussionmentioning
confidence: 99%
“…(2018) [ 7 ] Female/3 Abdominal distension 5.9 cm Right hepatic lobe Normal US, CT, and MRI Surgery N/A No (history of preterm birth) Martiniuc et al . (2018) [ 13 ] Female/40 Asymptomatic 4.2 cm × 5 cm Seg 3 Normal US and contrast enhanced CT Surgery No complications No Navarini et al . (2020) [ 6 ] Female/26 Acute abdomen and a palpable mass in the epigastrium 13 cm × 7 cm Left hepatic lobe N/A MRI Surgery N/A N/A Alfayez et al .…”
Section: Discussionmentioning
confidence: 99%
“…Focal nodular hyperplasia [1][2][3] is a benign liver tumor that usually does not require surgery [4]. The diagnosis is challenging for rare pedunculated forms of www.ijcasereportsandimages.com…”
Section: Discussionmentioning
confidence: 99%
“…To date, several authors have reported pedunculated cases of FNH, while most of them were associated with clinical symptoms that required intervention [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Recently, Akaguma et al [ 31 ] successfully performed laparoscopic surgery for pedunculated FNH in a female patient during pregnancy due to the increased risk of developing complications and severe clinical manifestations.…”
Section: Current Landscape Of Pedunculated Lesions In Fnhmentioning
confidence: 99%
“… The segmental distribution of pedunculated or exophytic FNH cases for the adult and pediatric population, based on the literature review [ 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. IVC, inferior vena cava; GB, gallbladder; FNH, focal nodular hyperplasia.…”
Section: Figurementioning
confidence: 99%